Performance of MYC, BCL2, and BCL6 break-apart FISH in small biopsies with large B-cell lymphoma: a retrospective Cytopathology Hematopathology Interinstitutional Consortium study - Menke, Joshua R.; Aypar, Umut; Bangs, Charles D.; Cook, Stephen L.; Gupta, Srishti; Hasserjian, Robert P.; Kong, Christina S.; Lin, Oscar; Long, Steven R.; Ly, Amy; Menke, Jacob A. S.; Natkunam, Yasodha; et al. (Frontiers in Oncology, 2024)
Fluorescence in situ hybridization (FISH) is an essential ancillary study used to identify clinically aggressive subsets of large B-cell lymphomas that have MYC, BCL2, or BCL6 rearrangements. Small-volume biopsies such as fine needle aspiration biopsy (FNAB) and core needle biopsy (CNB) are increasingly used to diagnose lymphoma and obtain material for ancillary studies such as FISH. However, the performance of FISH in small biopsies has not been thoroughly evaluated or compared to surgical biopsies. We describe the results of MYC, BCL2, and BCL6 FISH in a series of 222 biopsy specimens, including FNAB with cell blocks, CNBs, and surgical excisional or incisional biopsies from 208 unique patients aggregated from 6 academic medical centers. FISH had a low hybridization failure rate of around 1% across all specimen types. FISH identified concurrent MYC and BCL2 rearrangements in 20 of 197 (10%) specimens and concurrent MYC and BCL6 rearrangements in 3 of 182 (1.6%) specimens. A subset of paired FNAB and surgical biopsy specimens (either CNB or surgical excisional biopsy) from the same patient did not show any discrepancies for MYC or BCL2 FISH; of the 17 patients with 34 paired cytology and surgical specimens, only 2 of the 49 FISH probes compared (4% of all comparisons) showed any discrepancy and both were at the BCL6 locus. One discrepancy was due to necrosis of the CNB specimen causing a false negative BCL6 FISH result when compared to the FNAB cell block that demonstrated a BCL6 rearrangement. Ultimately, MYC, BCL2, or BCL6 FISH showed 96% concordance when compared across cytology and surgical specimens, suggesting FNAB with cell block is equivalent to other biopsy alternatives for evaluation of DLBCL or HGBCL FISH testing.